Development of Kickboxing Tool Media for Pencak Silat Athletes - Hilmy Aliriad; Beny Widya Priadana; Boy Eko Yoga Kurniawan (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The lack of assisting tools in improving the quality and accuracy of kicks also affects the enhancement of muscle mass and physical fitness of athletes in the Puslatcab Pagar Nusa Bojonegoro. This research aims to produce a development product of a kickboxing tool that assists in kicks for Pagar Nusa Pencak Silat athletes at the Puslatcab Pagar Nusa Bojonegoro. This study is a research and development (R&D) study that adapts the research and development strategies proposed by Borg and Gall. The data were analyzed using descriptive analysis techniques, consisting of descriptive feedback and assessment scores from all reviewers on each aspect of the product evaluation. The results of the conducted development research indicate that the product is a Kickboxing Tool Media for Pencak Silat Athletes at the Puslatcab Pagar Nusa Bojonegoro. It is suitable for use as a learning medium as it obtained a good average score. Based on the data obtained through the summary of three aspects, namely (1) accuracy aspect, (2) balance aspect, and (3) strength aspect, the small-scale study obtained a total score of 1800, while the large-scale study obtained 2771. Based on these research findings, it can be concluded that the average score for all questions is 2771 (Very Good).